Evaluation for potential drug-drug interactions in patients with community-acquired pneumonia - Živković Zarić, Radica; Suša, Romana; Stojadinović, Milorad; Lazić, Zorica; Čekerevac, Ivan; Kostić, Marina; Milovanović, Jasmina; Zarić, Milan; Janković, Slobodan (Archives of Pharmacy, 2022)
Drug-drug interactions (DDIs) are considered to be a very serious problem in pharmacology and pharmacy, usually correlating with multiple, concurrent use of drugs and vary from 3 to 5%, if a patient takes a small number of drugs, to 20% in patients taking more than 10 drugs. The aim of our study was to discover and analyze possible risk factors and possible protective factors related to the occurrence of potential drug-drug interactions (pDDIs) in a hospitalized patient with community-acquired pneumonia.Study had a prospective cross-sectional design, and it was carried out at the Pulmology Clinic, Clinical Center Kragujevac, Kragujevac, Serbia. The main outcome was the incidence of pDDIs in patients with community-acquired pneumonia checked by Lexicomp and Micromedex interaction checkers. The most severe pDDIs (Consider therapy modification D/ Avoid combination X/Major/Contraindicated) were found in 19 (20%) and 54 (58%) patients, according to Lexicomp and Micromedex, respectively. Patients with community-acquired pneumonia who were older, smokers, and with more prescribed drugs by more than a few independent prescribers had a higher risk to experience pDDIs. Possible protective factors were longer length of hospitalization, transfer from the Emergency Department, antiarrhythmic drugs as well as an anticoagulant therapy. In conclusion, patients with community-acquired pneumonia are under increased risk of pDDIs if they are older, smokers, and being prescribed more drugs by multiple independent doctors; those patients need special attention and routine check of pDDIs in order to reduce possible damage.